A Study of the Teaching and Learning English in the State Primary Schools in Luang Prabang District, Luang Prabang Province - PHANTHACHIT, Somchit; VONGSOUANGTHAM, Bounthieng; MAKESAVANH, Somchay (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to investigate the current conditions of English language teaching and learning at the primary education level, Grades 3-5, in Luang Prabang City, Luang Prabang Province. A quantitative research approach was employed. The sample consisted of 80 primary school teachers teaching Grades 3-5 from 22 state primary schools. The research instrument used for data collection was a five-level rating scale questionnaire focusing on four English language skills: listening, speaking, reading, and writing. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) to calculate the mean and standard deviation. The research findings revealed that: The overall English teaching and learning situation of primary school students in Grades 3-5 in Luang Prabang City, Luang Prabang Province, was at a middle level, with a mean score of 3.15 and a standard deviation of 0.75. Among the four language skills, listening had the highest mean score ( = 3.60; S.D = 0.77), followed by speaking ( = 3.30; S.D = 0.67), and reading ( = 3.24; S.D = 0.87). Writing had the lowest mean score, with ( = 2.47; S.D = 0.68)